COMPARATIVE ANALYSIS OF SERVICE QUALITY BETWEEN PUBLIC AND PRIVATE HOSPITALS, USING SERVQUAL MODEL: A CASE STUDY OF PESHAWAR, PAKISTAN - Abdul Rasool Khoso; Farhan Akhtar; Arshad Ali Narejo; Sajjad Ali Mallah; Kainat Vighio; Darya Khan Sanjrani (LPPM Akafarma Sunan Giri Ponorogo, 2022)
Health care industry is the integration and combination of various sectors offering quality and services to treat patients with preventive, curative, rehabilitative and palliative care. The healthcare system of Pakistan faces the challenges in providing quality as well as services as a whole, which is still supposed to be relatively poor to deliver satisfactory health care service to its citizens. Keeping in the view the nature of study, the researcher applied the quantitative method approach for obtaining the appropriate results, furthermore one sample T-test was performed to get the precise consequences of the data. For the particular purpose the SERVQUAL model which consists of five different service quality dimensions distinctively empathy, tangibility, assurance, timeliness, and responsiveness was applied. utilize to determine the local people/patients actual perception about the health care quality delivered by public and private sector hospital in Peshawar, Pakistan. A convenient based sample (n=150) was embraced from five hospital (3 public and 2 private) located in Peshawar. The results of the study identified the quality gaps in the service quality in various dimensions of SERVQUAL model. The result reveals that private hospitals are far better in term of empathy, tangibility, timeliness, and responsiveness, showing big difference between both hospitals. However, there is very little difference between the mean values of the service quality construct ‘assurance’ among the private having mean value (M=3.67; SD=.5258) and public (M=3.10; SD=7415) hospitals. It is because of qualified doctors with high expertise in the field of medicines/surgery and generally serving public hospitals as a permanent employees. Thus the study concluded that private hospitals are far away better from each perspective than the public due to the increasing trend of the resources availability. Since, majority of respondents who avail health care’s from the private hospitals were found satisfied in term of assurance, tangibility, timelines, responsiveness and tangibility as compared to the patients of public hospitals in Peshawar city. Finally the study recommends that, the public hospitals should implement feedback mechanism of its customers to get the actual picture of service quality and any deficiency in service quality should be serious considered for better outcomes. Furthermore government should also introduce value added rewards and facilities for the workforce of public hospitals to motivate them to better health service quality as for the sustainable development and betterment of public sectors